2000
DOI: 10.1017/s096025850000009x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dormancy and germination responses to temperature inCarduus acanthoides and Anagallis arvensisusing a screening system, and relationship with field-observed emergence patterns

Abstract: Experiments on the facultative winter annuals Carduus acanthoides and Anagallis arvensis were performed: (i) to determine thermal conditions that induce or release dormancy, (ii) to investigate to what extent changes in dormancy level resulting from those thermal conditions explain the seasonal pattern of emergence of these species, and (iii) to estimate required thermal time and base temperature for the germination of non-dormant seeds. Carduus acanthoides required high temperatures followed by decreasing tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 22 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…As expected, fluctuating temperatures promoted total seed germination in relation to that observed at constant temperature. This is in agreement with previous results of Soriano et al (1963) for B. campestris, Kruk and Benech-Arnold (2000) for C. acanthoides, and Forcella and Wood (1986) for C. vulgare. In contrast, our C. vulgare results under fluctuating temperatures were inconsistent with those published by Groves and Kaye (1989); the higher incubation temperatures used in their studies (20/ 308C) or a higher dormancy level in their seeds might account for these differences.…”
Section: Discussionsupporting
confidence: 94%
“…As expected, fluctuating temperatures promoted total seed germination in relation to that observed at constant temperature. This is in agreement with previous results of Soriano et al (1963) for B. campestris, Kruk and Benech-Arnold (2000) for C. acanthoides, and Forcella and Wood (1986) for C. vulgare. In contrast, our C. vulgare results under fluctuating temperatures were inconsistent with those published by Groves and Kaye (1989); the higher incubation temperatures used in their studies (20/ 308C) or a higher dormancy level in their seeds might account for these differences.…”
Section: Discussionsupporting
confidence: 94%
“…The germination test system (Washitani, ) consisted in exposing one batch of seeds to gradually increasing temperatures from 4°C to 36°C in steps of 4°C ( IT‐regime ) and a second batch to gradually decreasing temperatures from 36°C to 4°C ( DT‐regime ). As the germination rate is generally higher at higher temperatures in the physiological range, the duration of exposure differed depending on the prevailing temperature: 7 days at 4°C and 8°C, 5 days at 12°C and 16°C, 4 days at 20°C and 24°C, 3 days at 28°C and 2 days at 32°C and 36°C (modified from Kruk & Benech‐Arnold, , ). The number of germinated seeds was recorded immediately before a temperature change and at the end of the test.…”
Section: Methodsmentioning
confidence: 99%
“…For example, seeds of Portulaca oleracea L. have low seed dormancy at the end of winter, but incubating seeds at low temperatures under controlled conditions does not reduce the level of seed dormancy during the same period, showing that other factors interact in weed dormancy breaking (Kruk & Benech‐Arnold, ). It has also been observed that high temperatures do not induce secondary dormancy in P. oleracea , but rather cause the opposite effect and that the effect of temperature on the level of seed dormancy can be modulated by soil moisture (Kruk & Benech‐Arnold, , ). Moreover, once they have reached a low dormancy level, most weed seed populations require the termination of dormancy through exposure to light (Kruk et al ., ) and/or fluctuating temperatures (Thompson et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In weed species requiring environmental signals to terminate dormancy, the strength of the regulation of the emergence by the presence of a crop canopy will depend on the overlap between the ‘emergence window’ of the weed (i.e. the period at which the seed population displays minimum dormancy; Kruk & Benech‐Arnold 2000; Vleeshouwers & Kropff 2000) and the density of the crop canopy modifying these signals. The capacity to detect these changes in the thermal and light environments will also depend on the position of the seeds within the soil (Bliss & Smith 1985; Ghersa, Benech‐Arnold & Martinez‐Ghersa 1992), which will determine the probability of a seed germinating, emerging successfully and its relative time of emergence (Grundy, Mead & Burston 2003).…”
Section: Discussionmentioning
confidence: 99%